2005
DOI: 10.1097/01.ju.0000181815.63998.5f
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Single-Blind Comparison of Ureteral Stents Composed of Firm and Soft Polymer

Abstract: This randomized study showed no difference in the impact on patient quality of life between ureteral stents composed of firm or soft polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 10 publications
0
43
0
1
Order By: Relevance
“…Inclusion criteria were: (i) study assesses measures to treat or prevent SRS; (ii) standard indications for ureteral stenting; and (iii) use of USSQ, and reporting of at least urinary symptoms score and body pain score. However, aside from eight trials assessing drug treatment, which were already the subject of the metaanalyses described above, 12,14 just two further studies 25,26 met the inclusion criteria. Although many of the trials using the USSQ did not provide the actual numbers for USSQ total score and subscores, the remaining studies applied a multiplicity of tools to assess stent-related morbidity (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria were: (i) study assesses measures to treat or prevent SRS; (ii) standard indications for ureteral stenting; and (iii) use of USSQ, and reporting of at least urinary symptoms score and body pain score. However, aside from eight trials assessing drug treatment, which were already the subject of the metaanalyses described above, 12,14 just two further studies 25,26 met the inclusion criteria. Although many of the trials using the USSQ did not provide the actual numbers for USSQ total score and subscores, the remaining studies applied a multiplicity of tools to assess stent-related morbidity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…25 According to sample size calculation, 116 patients were analyzed using the USSQ as the primary outcome measure at 1 and 4 weeks after stent insertion. The authors found no significant differences regarding urinary symptoms, pain, general health and work performance at both times, and concluded that stent composition alone does not seem to influence patient comfort and overall ureteral stent experience.…”
Section: Stent Materials and Designmentioning
confidence: 99%
“…Stents have been associated with increased morbidity causing infection, (Riedl, Plas et al 1999) encrustation, (Paick, Park et al 2003) hematuria, (Damiano, Oliva et al 2002;Joshi, Newns et al 2003;Joshi, Chitale et al 2005) and discomfort (Joshi, Stainthorpe et al 2001;Joshi, Okeke et al 2002). The Ureteral Stent Symptom Questionnaire (USSQ) looks at different facets of life including sexual function which has been shown to be negatively affected by the presence of a stent (Sighinolfi, Micali et al 2007).…”
Section: Problems Arising From Stentsmentioning
confidence: 99%
“…Urinary stents contain various materials, and are available with different sizes, coatings and shapes to avoid unpleasant urinary symptoms and discomfort [8][9][10] . Joshi et al developed the ureteral stent symptom questionnaire (USSQ) to assess ureteral stent discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Joshi et al developed the ureteral stent symptom questionnaire (USSQ) to assess ureteral stent discomfort. The USSQ is a self-administered, multidimensional instrument that has six sections that address urinary symptoms, body pain, general health, work performance, sexual matters and additional problems [9,11] . Studies of stent-related symptoms using the USSQ reveal that stent length is the most important factor [12,13] .…”
Section: Introductionmentioning
confidence: 99%